AUTOGENOUS ARTERIOVENOUS ELBOW FISTULA FOR HAEMODIALYSIS AND UPPER EXTREMITY ISCHEMIA - Bachleda, Petr; Utikal, Petr; Kojecky, Zdenek; Drac, Petr; Köcher, Martin; Cerna, Marie; Zadrazil, Josef (Biomedical papers, 2007)
Background: The autogenous brachiocefalic or brachiobasilic arteriovenous elbow fistula is not considered to be only the secondary haemodialysis access. In patients with an unsuitable forearm vessel bundle, it is indicated as primary access and it is the method preferred to the fistula creation using a vascular prosthesis. Its rather rare complication is the development of upper extremity ischemia.Aim: To summarise current knowledge of this fistula type and its associated complications Methods: Review of the literature.Results: The creation and maturation of the fistula and occurrence of the steal syndrome is infl uenced by a number of factors. The analysis and awareness of such factors will provide for creation of a suitable fistula as well as for timely complication diagnostics and treatment.Conclusions: The autogenous elbow fistula utilising the brachial artery and the cephalic or basilic vein in the upper extremity represents a high-quality haemodialysis access. Its potential complication is the occurrence of the steal syndrome. Its occurrence and manifestations do not constitute indications for ligation of the access. The gathered information shows that a suitable surgical procedure can help meet the basic rule for haemodialysis access - resolving the ischemia and maintaining the access.
Keywords: Haemodialysis/Arteriovenous elbow fi stula/Steal syndrome